THE USING OF INTERACTIVE METHODS AT SCHOOL CLASSES AND SOME IDEAS FOR INTERACTIVE TEACHING (Archive of Conferences, 2022)
These days in education system of Uzbekistan a lot of changes have been seen. Radical transformation has altered the appearance of the modern world. Because of them we discover the best ways of teaching and learning. Whatever our beliefs about language teaching we need to be clear about what our attitude is to the major effective techniques which is the most important matter in methods of foreign language teaching and some technological innovation of recent years